Corporate Governance And Firm Performance: Empirical Evidence From Pakistan Banking Sector - Kehkashan Nizam (International Journal Of Economics Social And Technology, 2022)
Corporate governance is important in developing a culture of integrity in an ‎organization that enhances the performance of business resulting in sustainability in the ‎business of the organization. The purpose of this study is to investigate the impact of ‎corporate governance factors on bank performance in Pakistan. The data was ‎collected from 15 banks from the period of 2010 to 2020. The data was collected ‎from the financial reports of the banks. The dependent variable was returning on assets as a ‎proxy of firm performance and the independent variables were corporate governance ‎factors (namely, the board size, firm size, independent directors, CEO duality, and ‎leverage). The technique was applied for this research included the Co-integration test, ‎the Hausman test to determine Random or Fixed Effect, and the Panel Least Square Regression ‎to check the relationship between variables The result found that board size has ‎a significant effect on return on assets indicated that optimum board size in an ‎organization increases the ROA. The results found board independence has a significant ‎effect on return on assets indicating the independency of directors is involved in creating ‎greater value for shareholders. The results found that CEO/Chairman duality has ‎an insignificant impact on return on assets. The results found leverage has a significant ‎impact on return on assets indicating that having high leverage earns more profit. The ‎results found a positive impact of firm size on return on assets. Results can be ‎concluded that improvement in corporate practices increases the firm performance ‎shows the positive revenue generates by the company and the company used its assets ‎through business. Good CG practices make firm-healthy.